Anticorrosive Epoxy Coatings Enhanced with Rice Husk Derived-Graphene - Amalia, Dinda Putri; Riastuti, Rini (Jurnal Pendidikan Teknologi Kejuruan, 2022)
Coatings are the most common corrosion control practice. Therefore, it is very important to discover the most cost-effective and environmentally-friendly coating materials for sustainability. When dispersed in epoxy resin, graphene has barrier properties that improve the anticorrosive performance of the metal significantly. Graphene can be synthesized from agricultural waste. Herein, graphene derived from rice husk and epoxy resin was developed with solution mixing to prepare graphene-epoxy coating composites with enhanced anti-corrosive properties. X-ray diffraction, UV-vis spectroscopy, and scanning electron microscopy were used to characterize the synthesized graphenes. The anticorrosive properties of the coatings were characterized by potentiodynamic polarization and electrochemical impedance spectroscopy, which resulted in the corrosion resistance of synthesized graphene and commercial reduced graphene oxide being better than commercial graphene. The impedance and corrosion rate values of synthesized graphene are 1.77 x 105 Ω and 0.00011 mm/year.